Kutipan Ayat-ayat Al-Qur’an dan Kalimat Sufistik pada Beberapa Batu Nisan Makam Kuno di Indonesia - Tjandrasasmita, Uka (Lajnah Pentashihan Mushaf Al-Qur'an, 2009)
This writing studies the engraved QurÃ¢â‚¬â„¢anic verses and sufistic words on some of the ancient tombstones in Indonesia with the aim of tracing the purpose of this engraving,Ã‚Â and the source of verses and the chapter of the QurÃ¢â‚¬â„¢an being cited. It is from the number of the QurÃ¢â‚¬â„¢anic verses being cited on those tombstones that people are able to identify and predict the date the Muslim community in the Indonesian Archipelago (Nusantara) started to know the QurÃ¢â‚¬â„¢an and to read it. Further question is whether there is a tight connectionbetween one and other verses of the QurÃ¢â‚¬â„¢an which become the basic arguments of the SufisÃ¢â‚¬â„¢ thought. Further investigation and exploration is about the time the proofs of the sufistic words being engraved on the tombstone in Indonesia.